Екологічна небезпека промислових об’єктів запоріжжя - Казанцева, С. С. (ХНУРЕ, 2023)
This work provides an overview of the different methods and tools used for environmental monitoring, which allows for the identification of negative human impacts on the natural environment and the development of appropriate solutions. The control of the environment is crucial for the preservation of nature. Various methods and means are used to monitor the quality of air, water, soil, and other environmental components. One of the most effective methods is environmental monitoring, which involves the systematic measurement and analysis of environmental parameters.